The Effect of CEO Duality, Board Composition and Board Size on Organizational Performance of Companies Listed on the Kuala Lumpur Stock Exchange - Nordin Muhammad; D. Agus Harjito; Junaina Muhammad (Universitas Islam Indonesia, 2005)
This study examined the effect of CEO duality, board composition and board size on organizational performance of Bourse Malaysia or Kuala Lumpur Stock Exchange (KLSE) listed companies. For comparison purpose, this study examined these variables for main board companies as the proxy of large size companies, second board as the proxy for small size companies, and the whole market as proxy for developing country. This study employed 196 companies selected from the main board (96) and the second board (100) of KLSE and applied a simple regression analysis to describe the data of this study and MANOVA analysis model to test the effect of CEO duality, board composition and board size on organizational performance. We run these tests separately for main board, second board companies and the total market. The results indicated that the effects of multiple relationships between CEO du-ality and the three organizational performance variables (ROA, ROE, PER) before and after controlling by the age and industry are not significant for all three groups of board samples. While, the composition of outside directors was significant affects the firm performance for main board and combine board, but it is not significant for second board. Finally, board size is associated with higher firm performance. This evidence occurs only for main board. In gen-eral, the control variables, age and industry, do not affect significantly the relationships be-tween CEO duality, board composition, and board size and organizational performance.Key words: CEO duality, board composition, board size, firm performance.